2014
DOI: 10.1016/j.compstruct.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanical analysis of the in situ effect in polymer composite laminates

Abstract: A micro-mechanical finite element model of a composite sublaminate is proposed to study the mechanical response of ultra-thin plies, consisting of a representative volume element of a 90 • thin lamina in-between two homogenised ±θ • plies. Random fibre distributions, materially and statistically equivalent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 61 publications
(120 reference statements)
6
71
0
Order By: Relevance
“…In the present study, the individual carbon fibres are considered transversely isotropic and linear-elastic [22]. Following Melro et al [41], the diameter of the carbon fibres is the same in the entire RVE.…”
Section: Micro-mechanical Constitutive and Finite Element Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the individual carbon fibres are considered transversely isotropic and linear-elastic [22]. Following Melro et al [41], the diameter of the carbon fibres is the same in the entire RVE.…”
Section: Micro-mechanical Constitutive and Finite Element Modellingmentioning
confidence: 99%
“…An FE model of the thin-ply sublaminate is generated, consisting of three main parts: a micro-mechanical RVE of the 90 • ply, two adjacent homogenised 0 • plies, and the interfaces between the 90 • lamina and the homogenised plies [22]. The RVE of the 90 • ply includes a discrete representation of the fibres, matrix and interfaces between fibres and matrix.…”
Section: Micro-mechanical Constitutive and Finite Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the SRVE, many research studies [8][9][10][11][12][13][14][15][16][17] have been conducted to explore the intralaminar fracture of composite materials, which is the most common damage pattern in well-designed composite structures. Arteiro et al [18] further indicated that intralaminar fracture analysis at a microscopic scale was ideal because the modeling of damage presented higher resolution and freedom at this scale. Both fiber/matrix debonding and matrix micro-cracking, which are the two main damage modes of intralaminar fracture and are commonly classified into matrix cracks at a macroscopic scale, can be described subtly during the damage evolution in composites under transverse loading.…”
Section: Introductionmentioning
confidence: 97%
“…These parameters are based on experimental data [24] and also on previous micromechanical simulations [25,26].…”
mentioning
confidence: 99%